Ashwin Muralidharan IIT Madras
Last Activity: 13 Years ago
Hi Suchita,
Please note, here again the method of integration is the same as mentioned above.
Where 2lnx = lnx2
And ln(1+x2) - lnx2 = ln[(1+x2)/x2] = ln(1+1/x2)
And when x^2, is taken from the square root term, it cancels one x in the Dr, leaving x3.
So sub 1+1/x2 = t. Which will give dx/x3 = -dt/2
Please be careful with such calculations (previously there was a mistake while doing it very fast, and hence a mistake in the constant term. Please do take time while practicing questions to not make such very silly mistake).
Hope that helps.
All the best.
Regards,
Ashwin (IIT Madras).